Die Tragedy of the anticommons.: Kapitalistische Eigentumskritik im Patentwesen - Gröndahl, Boris (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 2002)
The patent system is one part of the triad of intellectual property, besieged by technological progress, globalisation and political criticism. In addition to the well-known argument that patents have unwanted moral or ecological consequences because they function, an immanent argument gains ground in the economic debate that they actually do not work as intended. In complex technologies such as biology, computers and software, the argument goes, patents tend to create a „tragedy of the anticommons“, stifling capitalist development.